Every day I sing the blues : the story of B.B. King - Shirley, David, 1955- (New York : F. Watts, 1995)
Traces the life of the dedicated and talented blues musician, from his birth in the Mississippi Delta in 1925 through the early 1990s.
Includes bibliographical references (p. 121-122) and index.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: King, B. B. -- Juvenile literature; King, B. B; King, B. B; Blues (Music); Blues musicians -- United States -- Biography -- Juvenile literature; African Americans -- Biography; Blues (Music); Musicians; African Americans -- Biography; Blues music; Musicians -- Biography